Kepribadian Peserta Didik SMK di Kota Bandung selama Pandemi COVID-19 - Yusef Abdul Aziz; Desi Nur Utamillah (Ma'soem University, 2022)
The aim to be obtained is the personality profile of SMK students in the city of Bandung after the COVID-19 pandemic. The population involved SMK in Bandung City using purposive sampling technique involving 109 students and showing the results of a number of 28 students in the low category and 6 students in the very low category, so that 34 people were identified as